"We're taking their brilliant minds": Science teacher expertize, meta‐discourse, and the challenges of teacher–scientist collaboration. Issue 2 (7th December 2019) - Shanahan, Marie‐Claire; Bechtel, Robert
Abstract: Programs that bring teachers and scientists together have continued to achieve attention as important potential contributions to science education. Often, however, those programs place teachers in the position of learner or apprentice to the scientists. This study examines a teacher–scientist partnership program (two project sites, two teachers and one scientist at each) that explicitly sought to challenge that model, bringing science teachers into science labs to share their expertize in a collaborative project. Using a framework that probes both the actors' and analysts' perspectives on expertize, this study examines whether the promise of the program's goal for mutual learning through collaboration can be met. Analysis of interviews and collaborative products focused on evidence of contributory and interactional expertize to understand if the project was able to bring together a group that was likely to be able to collaborate successfully. Metadiscourse was then probed to gain a deeper understanding of the ways in which they spoke of the expertize of their collaborators. Findings suggest that creating collaborative teams with ideal expertize matches is challenging and that collaborative efforts are complicated by the historic status of scientific and teaching expertizes especially in relation to outreach or knowledge translation projects.